10x+3(8+8x)=-6(x-4)

Simple and best practice solution for 10x+3(8+8x)=-6(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+3(8+8x)=-6(x-4) equation:


Simplifying
10x + 3(8 + 8x) = -6(x + -4)
10x + (8 * 3 + 8x * 3) = -6(x + -4)
10x + (24 + 24x) = -6(x + -4)

Reorder the terms:
24 + 10x + 24x = -6(x + -4)

Combine like terms: 10x + 24x = 34x
24 + 34x = -6(x + -4)

Reorder the terms:
24 + 34x = -6(-4 + x)
24 + 34x = (-4 * -6 + x * -6)
24 + 34x = (24 + -6x)

Add '-24' to each side of the equation.
24 + -24 + 34x = 24 + -24 + -6x

Combine like terms: 24 + -24 = 0
0 + 34x = 24 + -24 + -6x
34x = 24 + -24 + -6x

Combine like terms: 24 + -24 = 0
34x = 0 + -6x
34x = -6x

Solving
34x = -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
34x + 6x = -6x + 6x

Combine like terms: 34x + 6x = 40x
40x = -6x + 6x

Combine like terms: -6x + 6x = 0
40x = 0

Divide each side by '40'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| 4a+16=a+4 | | n^2+4n-32= | | -4=-y-4 | | .04n+29.99=42.51 | | 9t-27=16 | | 18*5= | | 0.2+9=8(0.4-1) | | 5+4x-14=x | | 145n+75=510 | | 10x+10=4x-2 | | 3-2x-3x=-12 | | 18/5/8= | | 4x-x=20+2+3 | | .2a=.5 | | 2+x=16 | | 5x-20+3x+8=180 | | 18*5/8= | | 2x-1=23 | | f=1.8(22)+32 | | 1500+594.25n=22893 | | -2d+2=-4(d-2) | | 9-y+6y=1 | | x+50+f=180 | | 2y=-x+2 | | 330+25n=455 | | n-7=-23 | | x-(-41)=-26 | | 4a^2-2a=0 | | 9n+324=648 | | -7-6x=5x+3-x | | x^2+16x+60= | | x+5y=42 |

Equations solver categories